The potential of Hibiscus sabdariffa seed extract and rice straw as coagulants-adsorbents for processing batik liquid waste - ANNISA SHANTI RAHMANI; MOHAMMAD MASYKURI; PRABANG SETYONO (Nusantara Bioscience, 2025)
Abstract. Rahmani AS, Masykuri M, Setyono P. 2025. The potential of Hibiscus sabdariffa seed extract and rice straw as coagulants-adsorbents for processing batik liquid waste. Nusantara Bioscience 17: 116-126. One of the efforts to reduce the content of heavy metals in this batik liquid waste is by applying the process of a combination of coagulation and adsorption. This process involves the use of the coagulant of Rosella Seeds Extracts (RSE) to neutralize the charge of the heavy metal ions, making them more likely to bind to the adsorbents from rice straw biomass. The adsorption then occurs, where the neutralized heavy metal ions are physically or chemically bound to the surface of the adsorbents, effectively removing them from the liquid waste. This study aims to determine the decrease in chromium metal levels (Cr6+) in artificial batik liquid waste using this coagulation-adsorption process with biocoagulants of rosella seed extracts combined with straw rice adsorbents. K2Cr2O7 solution was used as an artificial solution for batik liquid waste. The coagulation process was repeated 3 times to determine the optimum RSE biocoagulant, both doses, pH, and contact time. The first coagulation was carried out by mixing biocoagulant RSE into a 10 ppm K2Cr2O7 solution. The coagulation process was carried out in the same way at pH 2, 4, 5, 6, 8, and 10 using the optimal dose of biocoagulant. The result showed that the optimum dose of biocoagulant RSE was 30 × 103 ppm, with an absorbance value, and the percentage of chromium metal (Cr6+) was, respectively, 0.623 and 68.69%. Meanwhile, the optimum pH for RSE biocoagulant was at pH 2 (acid condition), with absorbance and the percentage of chromium metal (Cr6+) values being, respectively, 0.617 and 69.02%. These findings have potential applications in the field of environmental science and waste management, particularly in the development of effective and sustainable methods for treating industrial waste.